Protestant empire religion and the making of the British Atlantic world - Pestana, Carla Gardina (University of Pennsylvania Press, 2009)
Beginning with the role religion played in the lives of believers in West Africa, eastern North America, and western Europe in about 1500, author Carla Gardina Pestana shows how the Protestant Reformation helped to fuel colonial expansion as bitter rivalries prompted a fierce competition for souls. -- from publisher description.